Supporting Facilities of Dormitory Room at Modern Islamic Boarding Schools - Rahima Ramadhani Wiyatasari; Rangga Firmansyah; Ully Irma Maulina Hanafiah (Pendhapa, 2022)
Modern Islamic boarding schools are boarding schools which use the madrasa curriculum and teach general knowledge by combining the pesantren system and general education. Students, teachers, and school administrators live in dormitories and study in one area with various activities and the availability of existing facilities. In this study, it will focus on the supporting facilities provided by the dormitory in meeting the needs of its users, including the availability of a laundry room, dormitory dining room, male & female dormitories, dormitory musyrifah rooms, visitor living rooms, and housing for ustadz/ustadzah. By using qualitative research methods, this study will discuss the dormitory room facilities in modern Islamic boarding schools by taking samples from 4 Islamic boarding schools to find out what type of room typology is needed. Based on the results of the comparative data, it can be concluded that there are differences in the facilities and needs of Islamic boarding schools in Indonesia.